Antistaphyloccocal activity and antibiofilm activity of the extracts of Juglans neotropica Diels, Piper lineatum Ruiz & Pav. and Terminalia catappa L. - Julio R, Ruiz (2013)
In this study, was investigated the antistaphylococcal activity in vitro of ethanol and hydroalcoholic extracts of 3 peruvian medicinal plants: Juglans neotropica Diels (bark), Piper lineatum Ruiz & Pav. (leaves) and Terminalia catappa L. (leaves). The species were collected in the regions of Amazonas and Cajamarca, in Peru. Antistaphylococcal activity was assessed by microdilution method. The organisms used were bacteria Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis ATCC 12228. All extracts investigated showed significant activity against both bacteria with a minimum inhibitory concentration (MIC) of 125 to 500 μg/mL for Staphylococcus aureus, with increased activity of the ethanol extract of Juglans neotropica Diels, and of 250 to 500 μg/mL for Staphylococcus epidermidis, having greater activity the hydroalcoholic extract of Piper lineatum Ruiz & Pav. Phytochemical analysis confirmed the presence of terpene compounds, flavonoids and alkaloids on 6 extracts studied. The determination of Minimum Inhibitory Concentration of Biofilm (MICB) was performed by the plate microdilution method modified, using clinical isolates of Staphylococcus aureus and Staphylococcus epidermidis biofilm producing. Only hydroalcoholic and ethanolic extracts of leaves of Piper lineatum L. have significant activity with CMIB 500 μg/mL for both strains. The ethanol and hydroalcoholic extracts of Piper lineatum L may be good candidates to search of metabolites useful to combat biofilm-associated infections by Staphylococcus aureus and Staphylococcus epidermidis.